Application of web geospatial decision support system for Tanjung Karang rice precision irrigation water management - Mamodu, Maina Mohammed; Mohd Soom, Mohd Amin; Kamal, Md. Rowshon; Wayayok, Aimrun; Abd Aziz, Samsuzana; Abdullah, Mohd Yazid (2014)
Huge amount of water is lost especially at farm level due to lack of information on water demand and supply. The SWAMP (Soil Water Assessment and Management for Paddies) was built for managing paddy irrigation. This system was built using ArcGIS viewer for flex, Microsoft SQL database and ArcGIS Server 10.1 advance. The developed system is web based, interactive and user friendly graphic user interface by widgets technology and provide information concerning irrigation water demand and supply. Compute yields and performance indicators such as irrigation efficiency, relative water supply, water productivity index which are vital information for farmers and irrigation water managers. The results viewed in the form of thematic maps, tables, and charts for easy interpretation. SWAMP is simplified for non GIS expert to explore and retrieve information to make decision for best practices.